Sistem Informasi Sekolah Berbasis Web - Eka Puspita Sari; Asri Wahyuni; Narti Narti (Indonesian Journal on Software Engineering (IJSE), 2019)
Abstract: A system of data input and the grade of students who still use manual way namely by filling form of data on student and the grades of students in the form of paper sheet done by administration and teacher. Besides needed a place the immense storage, to find files need a require a long time, because that is the way are considered less effective. Websites is information in word wide web stored in different file as a page web. Academic information system web-based can manage academic information with more effective. The software used for develop information system web is PHP and MySQL for databases. Keywords : Php, MySQL, System, Information, Education